Intervenciones de enfermería prioritarias en el postoperatorio inmediato de amputación por pie diabético - Chisag Punina, Tannia Lucila (2026)
Amputations due to diabetic foot represent a serious complication that requires immediate, comprehensive care to prevent functional, emotional, and clinical sequelae. The lack of specific protocols in the immediate postoperative period limits the quality of nursing care during this critical phase. Objective: To standardize priority nursing interventions in the immediate postoperative period of patients undergoing amputation surgery due to diabetic foot through a systematic review of updated literature. Materials and Methods: This study was conducted using a qualitative approach with a non-experimental design and an exploratory, descriptive study applying the PRISMA method. Scientific articles published between 2020 and 2025 were analyzed. Inclusion criteria focused on clinically oriented, methodologically clear, and applicable studies. Results: Fifteen articles were identified that detailed priority interventions such as initial assessment, vital sign monitoring, pain management, stump care, glycemic control, pressure ulcer prevention, appropriate dressing application, bandaging, and emotional support for the patient. A standardization table was consolidated based on these interventions. Conclusions: The standardization of priority nursing interventions in the immediate postoperative period helps improve the quality of care, reduce complications, and promote functional and emotional recovery of patients amputated due to diabetic foot.